CIBERATIVISM AS A POTENTIAL INSTRUMENTALIZATION OF NEW TACTICS OF POLITIC PARTICIPATION - Braga, Julio Trevisam; Trevisam, Elisaide (Revista de Direito Brasileira, 2020)
Given the founding principles of the Democratic Rule of Law, in this research we have the objective to reflect on how the interactions of public power with popular sovereignty were subjugated by the imposition of financial governance over the state autonomy, putting on defeat position the popular trust in political representativeness, with the technological influence on political participation. Nowadays, as the traditional means of protest and participatory instruments have become limited in their effectiveness of popular pressure, the advent of cyberactivism as a political practice has become a potential tool in managing social conflicts. On the other hand, a new profile of internet users (ordinary citizens) comes into play, making our reflection necessary to understand how the Big Data tool was appropriated to direct public opinion around election campaigns. This research used the dialectical method and was carried out through a bibliographic survey, seeking to dialogue with historical and legal concepts to understand the problem and the development of the objectives.